Exploring The Social Conflict In The Novel Small Mercies By Dennis Lehane - Ingfijarotul Habibah; Winantu Kurnianingtyas Sri Agung (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study explores the presence of social conflict in literature as a reflection of real-world societal tensions. Literature has long been intertwined with society, often serving as a mirror that reveals the complexities of human relationships and communal life. Among the various types of conflict depicted in literary works, social conflict stands out due to its close connection to the human condition. As inherently social beings, individuals naturally encounter friction within their communities, making social conflict an inevitable and meaningful theme. In this context, literature not only reflects but also encourages critical engagement with social issues. It serves as an educational tool, particularly in the classroom, by raising awareness of the types of conflict that may arise in real-life contexts. This research applies Louis Kriesberg’s social conflict theory to analyze the novel Small Mercies by Dennis Lehane, offering a distinctive theoretical lens compared to prior studies. A qualitative method with narrative analysis was employed. Data were collected through documentation and analyzed using Creswell’s framework. The findings reveal three primary causes of social conflict in the novel: rank disequilibrium, changes in attainments and expectations, and power inequality. This study contributes to a deeper understanding of how literature portrays and critiques social dynamics.